2020
DOI: 10.2144/fsoa-2020-0149
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Natural Sleep and the Anesthetic State

Abstract: The anesthetic state and natural sleep share many neurobiological features and yet are two distinct states. The hallmarks of general anesthesia include hypnosis, analgesia, akinesia and anxiolysis. These are the principal parameters by which the anesthetic state differs from natural sleep. These properties are mediated by systemic administration of a combination of agents producing balanced anesthesia. The exact nature of anesthetic narcosis is dose dependent and agent specific. It exhibits a relative lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…General anesthesia and natural sleep induce similar behaviors. Therefore, their similarities have been discussed for a long time (Shafer, 1995;Date et al, 2020). The two conditions have both similar and different functional features.…”
Section: Neuronal Mechanism Of Sleep and Anesthesiamentioning
confidence: 99%
“…General anesthesia and natural sleep induce similar behaviors. Therefore, their similarities have been discussed for a long time (Shafer, 1995;Date et al, 2020). The two conditions have both similar and different functional features.…”
Section: Neuronal Mechanism Of Sleep and Anesthesiamentioning
confidence: 99%
“…isoflurane and ketamine-xylazine) and natural sleep in the context of our findings. In general, anesthesia serves as an excellent tool for inducing unconsciousness and may share many neurobiological processes with natural sleep [47][48][49] . However, anesthesia is not equivalent to natural sleep 50 and comparisons of these states are therefore inevitably flawed.…”
Section: Effect Of Anesthesia and Implications For Preclinical Dmrimentioning
confidence: 99%
“…The anesthetic state and natural sleep share many neurobiological features, yet they are distinct states [ 1 , 2 , 3 , 4 ]. While the anesthetic state is a pharmacologically induced, reversible state of unconsciousness, sleep is endogenously generated and involves the active suppression of consciousness by nuclei in the brainstem, diencephalon, and basal forebrain, and is dependent on homeostatic drive and circadian rhythm [ 5 ]. In contrast with sleep, in which there is a regular switch between non-rapid eye movement (NREM) and rapid eye movement (REM) sleep, once NREM sleep is established, in anesthesia at steady-state concentration, there is an alternation of brain states expressed by EEG oscillations that vary between delta, theta, alpha, and burst suppression [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anesthesia and sleep onset may differ in terms of the neurotransmitters and molecular targets involved, as well as the anesthetic used [ 5 ]. It has been suggested that the type of GABAergic inhibition observed in both sleep and anesthesia has subtle variation in terms of the preferred subunit of the GABA receptor as a target, as well as the differential distribution of the subunit throughout the central nervous system, which may determine the site of action of anesthetics and natural somnogens [ 5 ]. Evidence suggests that neurons controlling the sleep−wake states (VLPO/MnPO GABAergic or glutamatergic neurons) do not necessarily mediate general anesthesia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation